Getting to Know GIMF : The Simulation Properties of the Global Integrated Monetary and Fiscal Model - Anderson, Derek; Hunt, Benjamin; Kortelainen, Mika.; Kumhof, Michael (Washington, D.C. : International Monetary Fund, 2013)
The Global Integrated Monetary and Fiscal model (GIMF) is a multi-region, forward-looking, DSGE model developed by the Economic Modeling Division of the IMF for policy analysis and international economic research. Using a 5-region version of the GIMF, this paper illustrates the model's macroeconomic properties by presenting its responses under a wide range of experiments, including fiscal, monetary, financial, demand, supply, and international shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet